2017
DOI: 10.18632/oncotarget.17767
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed commencement of adjuvant chemotherapy (eight or more weeks) on survival in stage II and III colon cancer: a national population-based cohort study

Abstract: BackgroundTo examine the impact of chemotherapy delay on survival in patients with stage II or III colon cancer and the factors associated with the delay (≥8 weeks) of adjuvant chemotherapy.MethodsPatients undergoing curative resection and adjuvant chemotherapy in a national population-based cohort were included.ResultsAmong 5355 patients, 154 (2.9%) received chemotherapy more than 8 weeks after surgery. Based on a multivariate analysis, the risk factors associated with chemotherapy delay ≥8 weeks were older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
(80 reference statements)
1
27
0
Order By: Relevance
“…Previously published papers reported improved outcomes after adjuvant chemotherapy without an increase in OS [ 10 , 31 ] confirming also that elderly patients are often oncologically undertreated [ 32 ]. Nevertheless, initiation of chemotherapy within 6–8 weeks is a recognized prognostic factor for OS [ 33 , 34 ]. Unfortunately, the small sample of patients receiving chemotherapy after surgery in this series precluded a subgroup analysis of the impact of the different chemotherapy regimens and use of molecular targeted therapies.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published papers reported improved outcomes after adjuvant chemotherapy without an increase in OS [ 10 , 31 ] confirming also that elderly patients are often oncologically undertreated [ 32 ]. Nevertheless, initiation of chemotherapy within 6–8 weeks is a recognized prognostic factor for OS [ 33 , 34 ]. Unfortunately, the small sample of patients receiving chemotherapy after surgery in this series precluded a subgroup analysis of the impact of the different chemotherapy regimens and use of molecular targeted therapies.…”
Section: Resultsmentioning
confidence: 99%
“…86 This observation has been confirmed by other groups. 87,88 However, population-based studies have shown that adjuvant chemotherapy might still provide some benefit, even with delays up to 5e6 months, 89,90 but it seems that the benefit of adjuvant chemotherapy is minimal or completely lost if treatment is started >6 months after surgery. pathological risk characteristics, patient comorbidity and risk assessment.…”
Section: Timing Of Adjuvant Chemotherapymentioning
confidence: 99%
“…Additionally, delaying some therapies with a curative intent may lead to adverse outcomes in cancer patients. A decrease in overall survival has been reported among patients with locally advanced breast cancer who had a delayed adjuvant or neoadjuvant chemotherapy[ 94 - 96 ], In stage II-III colon cancer, delaying adjuvant chemotherapy was also found to have a worse overall survival[ 97 , 98 ]. Similarly, delayed radiotherapy also has deleterious effects.…”
Section: Cancer Patients In Pandemicmentioning
confidence: 99%